2018
DOI: 10.14569/ijacsa.2018.091024
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mobile Forensic Tools Evaluation on Android-Based LINE Messenger

Abstract: The limitation of forensic tool and the mobile device's operating system are two problems for researchers in mobile forensics field. Nevertheless, some kinds of forensic tools testing in several devices might be helpful in an investigation. Therefore, the evaluation of forensic tool is one gate to reach the goal of a digital forensics study. Mobile forensics as one of the digital forensics branch that focusing on data recovery process on mobile devices has some problems in the analytical ability because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The TF-IDF formula is multiplying the weight of TF with the IDF of each word. The TF-IDF formula can be seen in (3).…”
Section: Tf-idf Weightingmentioning
confidence: 99%
See 1 more Smart Citation
“…The TF-IDF formula is multiplying the weight of TF with the IDF of each word. The TF-IDF formula can be seen in (3).…”
Section: Tf-idf Weightingmentioning
confidence: 99%
“…A report released by the RSA Anti-Fraud Command Center (AFCC) states that from 2013 to 2015, there was an increase in cybercrime activity reaching 173% worldwide with total losses reaching US$ 325 billion. The report also reported that in 2015 45% of transactions were carried out through mobile channels, while 61% of fraud occurred through mobile devices [3]. Social media such as Facebook, WhatsApp, Twitter, etc., is one of the ways for someone to do cybercrime.…”
Section: Introductionmentioning
confidence: 99%
“…The IM application is one of the messaging applications that replaces the role of Short Message Service (SMS) which is very popular today [3] [4], one of which is Line. Line is an IM application that can be used on mobile devices and computers [5]. Line has many features such as text / voice chat, photo, sending video and locaton, video call, group chat and timeline.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [17] conducted forensic analysis of Line applications on Sony Xperia Z devices using Oxygen Forensic and MOBILedit. The researcher used NIST forensic methodology to conduct forensic analysis.…”
Section: Introductionmentioning
confidence: 99%